2014
DOI: 10.1111/ijs.12332
|View full text |Cite
|
Sign up to set email alerts
|

How to Unfasten the Spanish Stroke Belt? Andalusia Chooses Research

Abstract: Andalusia in southern Spain, one of the largest regions in the European Union, has made a profound economic and social transformation that has led to establishment of a modern universal public health care system. However, due to its high stroke mortality rates, Andalusia is still known as the 'Spanish Stroke Belt'. To fight these figures, successive initiatives culminated in the launch of the Andalusian Plan for Stroke Care, to be developed during the period of 2011 to 2014. In addition, involved professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Prior studies have shown that women are less likely than men to be investigated with standard diagnostic tests and that women admitted to hospitals with stroke are less likely to receive defect-free care. 11 In our study, women had fewer neuroimaging tests after stroke. This fact causes women to have a higher percentage of misdiagnoses.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Prior studies have shown that women are less likely than men to be investigated with standard diagnostic tests and that women admitted to hospitals with stroke are less likely to receive defect-free care. 11 In our study, women had fewer neuroimaging tests after stroke. This fact causes women to have a higher percentage of misdiagnoses.…”
Section: Discussionmentioning
confidence: 51%
“…In this way, inequalities between areas have been reduced since it has been achieved that almost the entire population is less than an hour away from a center where stroke treatment can be performed. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Andalusia has been called the "Spanish Stroke Belt" on account of its extremely high stroke mortality rate, which is as high as 54 per 100,000 inhabitants and exceeds those of other Spanish regions by up to 50%. 11 In addition to the classical factors such as patient age and type of stroke, another factor contributing to this increased mortality rate might be the geographic dispersion of the region, with 3 million inhabitants (36% of the population) living outside urban areas in villages with small populations.…”
Section: Introductionmentioning
confidence: 99%
“…A telestroke network was created to improve this statistic by reorganizing and improving stroke care in the region. In this way, inequalities between areas have been reduced 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that women are less likely than men to be investigated with standard diagnostic tests and that women admitted to hospitals with stroke are less likely to receive defect-free care 11 . In our study, women had fewer neuroimaging tests after stroke.…”
Section: Discussionmentioning
confidence: 99%